2001
DOI: 10.1002/mrm.1160
|View full text |Cite
|
Sign up to set email alerts
|

Localized two‐dimensional shift correlated MR spectroscopy of human brain

Abstract: A two-dimensional (2D) chemical shift correlated MR spectroscopic (COSY) sequence integrated into a new volume localization technique (90°-180°-90°) is proposed for whole-body MR spectroscopy (MRS).Due to the recent improvements in the design of B 0 gradient and RF coils, 1 H MR spectra have been recorded in human brain with excellent water suppression using short TE, as short as 15 ms, and several cerebral metabolites have been identified (1-4). During the past decade alterations in several metabolites, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
244
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 200 publications
(254 citation statements)
references
References 46 publications
(99 reference statements)
8
244
0
Order By: Relevance
“…For in vivo measurements, MR spectroscopic data is complicated by the inherent overlap and complex shapes of the signals of interest. Methods to improve detection of specific spectral contributions include spectral editing [4,18,28,33,[46][47][48]; spectral fitting using constrained parametric model optimization and incorporating a priori metabolic information [6,7,23,24,31,35,40,45,50]; and use of multidimensional spectral acquisition methods [42][43][44]. In all of these areas of research, spectral simulation methods are becoming an increasingly important tool.…”
Section: Introductionmentioning
confidence: 99%
“…For in vivo measurements, MR spectroscopic data is complicated by the inherent overlap and complex shapes of the signals of interest. Methods to improve detection of specific spectral contributions include spectral editing [4,18,28,33,[46][47][48]; spectral fitting using constrained parametric model optimization and incorporating a priori metabolic information [6,7,23,24,31,35,40,45,50]; and use of multidimensional spectral acquisition methods [42][43][44]. In all of these areas of research, spectral simulation methods are becoming an increasingly important tool.…”
Section: Introductionmentioning
confidence: 99%
“…However, Leifbritz et al hypothesized that water bound to a protein or located in its boundary transfers magnetization to bulk water via proton chemical exchange or cross relaxation to bulk water, which transfers magnetization to the amino group via chemical exchange and by dipolar relaxation to the methyl group (10). It was also concluded that both creatine and phosphocreatine contribute to the MT effect since it does not change after death in animal studies (11).Nonselective excitation/detection of several metabolites using spatially resolved two-dimensional (2D) MRS techniques has been successfully demonstrated recently on whole-body 1.5-and 3-T MRI scanners (12)(13)(14)(15). Coherent interactions such as chemical shift and J-coupling between protons of metabolites and lipids lead to different 2D diagonal and cross peaks showing the connectivities between protons of tissue metabolites.…”
mentioning
confidence: 99%
“…Nonselective excitation/detection of several metabolites using spatially resolved two-dimensional (2D) MRS techniques has been successfully demonstrated recently on whole-body 1.5-and 3-T MRI scanners (12)(13)(14)(15). Coherent interactions such as chemical shift and J-coupling between protons of metabolites and lipids lead to different 2D diagonal and cross peaks showing the connectivities between protons of tissue metabolites.…”
mentioning
confidence: 99%
“…The 3 in coil was placed directly on the forehead of the subject and a 3 Â 3 Â 3 cm 3 voxel was positioned to the left side of the forehead, just above the eye to be closer to the left frontal white matter region. The 2D L-COSY sequence consisted of three slice-selective rf pulses (901, 1801, and 901) for the volume localization and the coherence transfer necessary for 2D-correlated spectroscopy (Thomas et al, 2003(Thomas et al, , 2001. A CHESS sequence was used for global water suppression prior to volume localization.…”
mentioning
confidence: 99%
“…The PCh peak overlaps with glycerylphosphocholine, and the Pe peak overlaps with glycerophosphethanolamine. The assignments of these peaks were guided by the 2D L-COSY spectra of individual phantom solutions of several metabolites (Thomas et al, 2001) and a previous report on the 1D MRS chemical shifts (Govindaraju et al, 2000). …”
mentioning
confidence: 99%